Pengaruh Atribut Mice Terhadap Kunjungan Wisatawan di Kota Bandung - Ratna Sholihah Sarha; Gilang Pratama Putra; Dally Nur Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aimed to analyzed the influence of MICE attributes on tourist visits in Bandung by adapting the dimensions of MICE destination guideline and criteria developed by the Ministry of Tourism and Creative Economy in 2017 as independent variables. This research used quantitative research method with multiple linear regression analysis. The data obtained came from distributing questionnaires via Google form to respondents who had visited Bandung, and a sample of 100 people was taken. Based on the result of this research, MICE attributes in Bandung have met the needs of tourist so that they can increase tourist visits to Bandung, especially MICE tourist. MICE attributes have a significant influence simultaneously on tourist visits. The dimension of attraction an ancillary service partially have positive influence and significant influence on tourist visit, while accesibiliry, activities, amenities, and affordability do not have a positive influence and is not significant on tourist visists in Bandung.